The Role of Programmed Necrosis in Colorectal Cancer - Yu, Yidong; Gámez Belmonte, Maria de los Reyes; Patankar, Jay; Liebing, Eva; Becker, Christoph (Cancers, 2022)
Simple Summary Necrosis is a type of cell death characterized by plasma membrane rupture and the induction of inflammation. This review focuses on colorectal cancer and outlines the role of programmed necrosis in tumor development. Potential strategies for anti-tumor treatment via targeting programmed necrosis are also discussed. For quite a long time, necrosis was considered a chaotic and unorganized form of cell death. However, studies conducted during the past few decades unveiled multiple types of programmed necrosis, such as necroptosis, pyroptosis and ferroptosis. These types of programmed necrosis have been shown to play crucial roles in mediating pathological processes, including tumorigenesis. Almost all key mediators, such as RIPK3 and MLKL in necroptosis, GSDMD and caspase 1/11 in pyroptosis and GPX4 in ferroptosis, are highly expressed in intestinal epithelial cells (IECs). An aberrant increase or decrease in programmed necrosis in IECs has been connected to intestinal disorders. Here, we review the pathways of programmed necrosis and the specific consequences of regulated necrosis in colorectal cancer (CRC) development. Translational aspects of programmed necrosis induction as a novel therapeutic alternative against CRC are also discussed.
CRIS-Team WoS Importer:2022-09-16